The relationship between success of ISO 9000 implementation and organizational commitment : a case study at Universiti Malaysia Sabah - Talib Abdullah Shani (2006)
The education industry is undergoing rapid changes. The private sector has become a major player. Consequently, competition and quality have become key issues. The certification to ISO 9000 is one of the ways to project the quality of the offering. The implementation of ISO 9000 standards to education has, however, provoked a variety of reaction. Van den Berghe (1997) states that "ISO 9000 is not an appropriate goal for any organization in any circumstance". This indicates that the implementation of ISO 9000 may not be the best option for all educational institutions (Thonhauser, T.L., 2005). Therefore, the main objective of this study is to investigate the success of ISO 9000 implementation and its relation to the organizational commitment, by focusing to Universiti Malaysia Sabah (UMS) as a case study. The current literature surrounding ISO 9000 implementation in education indicates that the success of ISO 9000 implementation is debatable in educational institutions, especially in the universities. This study did not attempt to end the debate over the success of ISO 9000 implementation in UMS, but moreover to investigate whether there is a significant relationship with organizational commitment. This study is a quantitative survey research conducted in the natural environment of the selected organization (UMS), using questionnaire. A purposive sampling technique was utilized in the selection of the samples for the study. The total number of respondents' in this study was 152 employees from various level in UMS (academic and non academic staff), of which 86 of respondents' were males and 66 females. Data was analyzed using Statistical Package for Social Science Program (SPSS) version 12.0.1. Descriptive analysis, reliability, multiple regression, correlation and hierarchical regression analysis were applied to manage the data. The findings indicated that there is a positive and significant relationship between the independent variables (success of ISO 9000 implementation and its elements) with organizational commitment. However, results of the moderating effect on job position and education level relationships were not significant. This study would be useful to understand the effect of success on ISO 9000 implementation to the organizational commitment and furthermore to help promote mutual understanding between top management and employees and further strengthen cooperation within the organization.